Genome‐wide association study of tuberculosis in the western Chinese Han and Tibetan population. Issue 2 (29th March 2023) - Bai, Hao; Song, Mengyuan; Lei, Shikun; Jiao, Lin; Hu, Xuejiao; Wu, Tao; Song, Jiajia; Liu, Tangyuheng; Peng, Wu; Zhao, Zhenzhen; Meng, Zirui; Ying, Binwu
Abstract: Tuberculosis (TB) remains a serious global public health threat. Accumulated evidence has demonstrated that human susceptibility to TB has a strong genetic basis. And different susceptibility single nucleotide polymorphisms (SNP) have been reported in different studies. To gain greater insight into the host susceptibility to TB, we perform a two‐stage genome‐wide association study to identify the susceptible loci of TB. In the discovery stage, 3116 (1532 TB patients and 1584 healthy controls) and 439 (211 TB patients and 228 healthy controls) individuals were genome‐wide genotyped from a western Chinese Han and Tibetan population, respectively. Based on the additive genetic model, we discovered 14 and three independent loci that had potential associations with TB susceptibility in the Chinese Han and Tibetan populations, respectively ( p  < 1 × 10 −5 ). Furthermore, we conducted an imputation‐based meta‐analysis on another two East Asia cohorts to replicate our findings. We identified one independent locus harbored by the human leukocyte antigen ( HLA ) class II genes that was genome‐wide significantly associated with TB (lead SNP rs111875628 with a p‐ value of 2.20 × 10 −9 ). Our findings suggest a novel mechanism of the interaction with the HLA class II genes and reinforce the importance of the HLA class II alleles in response to TB. Abstract : This genome‐wide association study discovered 14 and 3 independent loci that had potential associations with Tuberculosis (TB) susceptibility in the Chinese Han and Tibetan populations, respectively ( p  < 1 × 10 ‐5 ). Further imputation‐based meta‐analysis on another two East Asia cohorts verified one independent locus harbored by the human leukocyte antigen class II genes that was genome‐wide significantly associated with TB (lead single nucleotide polymorphism rs111875628 with a p‐ value of 2.20 × 10 ‐9 ).